2005
DOI: 10.1016/j.biopsych.2005.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Striatum/Nucleus Accumbens Activation to Smoking-Related Pictorial Cues in Smokers and Nonsmokers: A Functional Magnetic Resonance Imaging Study

Abstract: Background-Converging evidence from several theories of the development of incentivesensitization to smoking-related environmental stimuli suggests that the ventral striatum plays an important role in the processing of smoking-related cue reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
227
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(253 citation statements)
references
References 59 publications
22
227
2
2
Order By: Relevance
“…22,58 The ventral striatum and prefrontal cortex appear to have integrated and differentiated roles in the process of reward signalling and aversive affects of nicotine administration and withdrawal. [59][60][61][62] However, whether or not the differentiation in processing rewarding and aversive drug experiences varies among dopamine receptor subtype, or how this might translate to lack of apparent pharmacogenetic effects on smoking cessation of DRD4 genotype compared with DRD2 genotype, would require further study.…”
Section: Discussionmentioning
confidence: 99%
“…22,58 The ventral striatum and prefrontal cortex appear to have integrated and differentiated roles in the process of reward signalling and aversive affects of nicotine administration and withdrawal. [59][60][61][62] However, whether or not the differentiation in processing rewarding and aversive drug experiences varies among dopamine receptor subtype, or how this might translate to lack of apparent pharmacogenetic effects on smoking cessation of DRD4 genotype compared with DRD2 genotype, would require further study.…”
Section: Discussionmentioning
confidence: 99%
“…The vSTR, which includes the nucleus accumbens, is sensitive to both reward magnitude (Galvan et al, 2005) and probability (Pagnoni et al, 2002) and has been shown to be active in response to drug cues (David et al, 2005;Kilts et al, 2001). At the same time, another event-related study observed decreased cue reactivity in the nucleus accumbens of smokers (Due et al, 2002).…”
Section: Cravingmentioning
confidence: 99%
“…Insulae are important in mediating autonomic responses to drugs of abuse and their predictors and thus were examined in the analysis (Bechara et al, 2000;Garavan et al, 2000). Lastly, we predicted that smoking cues would activate the fusiform gyrus, as it plays a role in attention, and has been activated in previous nicotine cue reactivity studies (David et al, 2005;Due et al, 2002;Wilson et al, 2005). We hypothesized that increases in perfusion in ventral medial prefrontal and deep limbic structures (amygdala, insula, and ventral striatum), regions important in mediating responses to drug cues, would correlate with subjective craving scores.…”
Section: A Priori Cns Regions Of Interestmentioning
confidence: 99%